EFFECTIVENESS OF PANCASILA AND CITIZENSHIP EDUCATION LEARNING - Sihombing, Grace Kelly Hadiputri; Lubis, Laila Nurfitrah; Oktavianda, Melti (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The national urgency of Pancasila and Citizenship Education in overcoming the moral decadence faced by the nation. Character education in higher education, especially through the mandatory general courses of Pancasila and Citizenship Education, is a solution to form good character in students in accordance with the mandate of Law 12 of 2012 concerning Higher Education. The research was conducted in several universities in Pontianak City, focusing on the effectiveness of the courses in fulfilling the effectiveness of the law regarding the implementation of the mandatory curriculum of Pancasila and Citizenship Education courses in the context of local society. The research uses a qualitative approach with a descriptive analysis method. The results of the research will be in the form of reports and articles proposed for publication in accredited national journals. The purpose of this study is to show the effectiveness of the Pancasila and Citizenship Education courses in forming student character, as well as what strategies have been carried out by universities to achieve the effectiveness of MKWK learning in universities in Pontianak City. The results of the research are expected to contribute to building closer cooperation between the government and universities in strengthening character education. This can be done through knowledge exchange, curriculum development, regulations, or other supporting programs to strengthen character learning at the tertiary level.